Culture, diversity and heritage: major studies - Arizpe, Lourdes (SpringerBriefs on Pioneers in Science and Practice,, 2015)
The texts presented in this book trace the rise of culture as a major concern for development, international diplomacy, sustainability and national politics over the past two decades. As a major participant in anthropological field research, advocate for cultural freedom and decision-maker in international programs on culture, the author gives a firsthand account of the trade-offs, the contradictions and the management of consensus in these fields. She argues that the constitutive, functional and instrumental aspects of cultural narratives call for a more in-depth understanding of knowledge, leading to cultural and social sustainability in the framework of a "new worlding". Many of the texts gathered here were presented at the United Nations General Assembly and other high-level international meetings. Most of the texts are unpublished; some were first published in Spanish and are now available in English for the first time.